Effect of hydrocortisone versus methylprednisolone on clinical outcomes in oncology patients with septic shock. (January 2021) - McDonnell, Emily; Collins, Reagan; Hernandez, Mike; Brown, Anne Rain T.
Background: Corticosteroids are used as adjunctive treatment of critical illness-related corticosteroid insufficiency in patients with septic shock. This study aims to compare the impact of hydrocortisone versus methylprednisolone on duration of septic shock in critically ill oncology patients. Methods: Single-center, retrospective cohort study of adult patients receiving hydrocortisone ≥200 mg/day or methylprednisolone ≥40 mg/day with septic shock. The primary outcome was time to shock reversal defined as time to systolic blood pressure ≥90 mmHg without vasopressors for ≥24 h. Results: Eighty-eight patients were included, 49 patients received hydrocortisone and 39 patients received methylprednisolone. Solid tumor malignancy was more common in the hydrocortisone group, while hematological malignancy was more common in the methylprednisolone group (p = 0.009). Time to shock reversal was similar between hydrocortisone and methylprednisolone groups (72.4 versus 70.4 h; p = 0.825). Intensive care unit mortality occurred in 51.02% versus 53.85% of patients in hydrocortisone versus methylprednisolone, respectively (p = 0.792). Patients who received methylprednisolone had higher rates of mechanical ventilation (89.74% versus 55.1%, p < 0.001) and longer intensive care unit and hospital lengths of stay (4.2 versus 11.4 days and 14.3 versus 25.7 days; p < 0.001) compared to hydrocortisone. No differences were seen in incidence of steroid-related adverse effects between groups. Conclusions: In oncology patients with septic shock, the use of hydrocortisone versus methylprednisolone does not appear to affect time to shock reversal.